2018
DOI: 10.1038/s41593-018-0167-4
|View full text |Cite
|
Sign up to set email alerts
|

The locus coeruleus drives disinhibition in the midline thalamus via a dopaminergic mechanism

Abstract: The paraventricular nucleus of the thalamus (PVT) is increasingly being recognized as a critical node linking stress detection to the emergence of adaptive behavioral responses to stress. However, despite growing evidence implicating the PVT in stress processing, the neural mechanisms by which stress impacts PVT neurocircuitry and promotes stressed states remain unknown. Here we show that stress exposure drives a rapid and persistent reduction of inhibitory transmission onto projection neurons of the posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
171
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(191 citation statements)
references
References 47 publications
20
171
0
Order By: Relevance
“…After social defeat stress, which involves dopamine signaling in the NAc for the acquisition of stress responses, D 2 R‐SPN exhibited changes in the AMPA/NMDA ratios when mice were susceptible, suggesting that synaptic changes support sustained stress responses. A recent report showed that dopamine‐β‐hydroxylase‐positive neurons in the locus coeruleus project to the paraventricular thalamus to facilitate stress responses via dopamine release . According to the results of the study, stress caused a persistent decrease in inhibitory input to paraventricular thalamus neurons, which suggested that D 2 R‐dependent LTD underlies such persistent effects.…”
Section: Cellular and Synaptic Bases For Sustained Effectsmentioning
confidence: 62%
“…After social defeat stress, which involves dopamine signaling in the NAc for the acquisition of stress responses, D 2 R‐SPN exhibited changes in the AMPA/NMDA ratios when mice were susceptible, suggesting that synaptic changes support sustained stress responses. A recent report showed that dopamine‐β‐hydroxylase‐positive neurons in the locus coeruleus project to the paraventricular thalamus to facilitate stress responses via dopamine release . According to the results of the study, stress caused a persistent decrease in inhibitory input to paraventricular thalamus neurons, which suggested that D 2 R‐dependent LTD underlies such persistent effects.…”
Section: Cellular and Synaptic Bases For Sustained Effectsmentioning
confidence: 62%
“…For these studies, the effects of PrL-PVT manipulation were examined early in Pavlovian training, when Pavlovian cues are known to evoke a DA response in the NAc to a different degree in STs and GTs 28,56 . Although we expected to observe more robust behavioral effects during this period, we found that stimulation of the PrL-PVT pathway early in Pavlovian training did not affect the behavior of STs, nor did it significantly affect extracellular It has become increasingly apparent in recent years that the PVT and its associated circuitry play an important role in motivated behaviors, including those related to addiction and anxiety-related disorders 16,33,[57][58][59][60][61][62][63][64][65][66][67][68] . Here, we honed in on the PrL-PVT pathway and exploited an animal model of individual differences in cue-reward learning to demonstrate that this circuit acts as a top-down control mechanism to suppress the attribution of incentive value to a food-paired cue.…”
Section: Discussionmentioning
confidence: 72%
“…Neurons in the LC are topographically organized based on their widespread efferent projections 46,47 , and circuit-based approaches reveal functional specificity of sub-populations of LC neurons based on their target projection regions 5,[12][13][14][15][16]18,19,67,68 . LC neurons appear to form neuronal ensembles, which can be activated in response to isolated sensory stimuli 67,69 .…”
Section: Adrenoceptor Distribution As An Organizing Principle Affordimentioning
confidence: 99%